Impact of Intimate Partner violence on ever married women and utilization of antenatal care services in Tanzania - Kabir, Russell; Majumder, Anwarul Azim; Arafat, SM Yasir; Chodwhury, Rocky Khan; Sultana, Shireen; Ahmed, SM Moslehuddin; Monte-Serrat, Dioneia Motta; Chowdhury, Esmot Zarin (Journal of College of Medical Sciences-Nepal, 2018)
Background and Objectives: Sub Saharan Africa region is considered as one of the deprived regions of this world and women from this part of the world are suffering from intimate partner violence. This study was undertaken to assess the impact of intimate partner violence on utilization of antenatal care services among the ever married women. Materials and Methods: This is a descriptive cross-sectional study design. The data used in this research was extracted from the Tanzania Demographic Health Survey 2015-16. A total of 13, 266 women were interviewed. Results: The mean age of the respondents is 28.69 years. About 74% women visited antenatal care services more than 4 times. Logistic regression results indicate that the middle-aged adult women (35-49 years age group) were identified having lower odds (Odds ratio: 0.807, 95% CI: 0.693-0.940, P<0.001) than women in younger age group. Women who did not complete their secondary education were less likelihood to experience IPV (Odds ratio: 0.705, 95% CI: 0.540-0.922, P<0.010). Conclusion: Intimate partner violence is one main challenge to women’s health and wellbeing during pregnancy period. Proper implementation and community based interventions to support pregnant women to seek antenatal care services and to raise awareness regarding intimate partner violence are advocated.